PERANAN KOMISI INFORMASI DALAM MENSOSIALISASIKAN PERATURAN KOMISI INFORMASI UNTUK KETERBUKAAN INFORMASI PUBLIK DI PROVINSI BALI: - - Dewa Nyoman Suardana; Ni Made Yuliani; I Made Dian Saputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This openness of information must be guarded simultaneously by the public and public bodies, openness of information can bring prosperity to the community, and become a tool towards accelerating development. If this information disclosure is implemented, the public will know many things, human resources will increase which will then become an asset for the government to support the acceleration of the realization of government programs. During the 13 (thirteen) years of promulgation, the public and public bodies have not followed up on it massively. Researchers are interested in researching